PERANCANGAN 3D VIDEO GAME AKSI BERCORAK BUDAYA INDONESIA DENGAN PENDEKATAN UI/UX - Hadi, Farhan Hidayatul; Nadya, Nadya (Jurnal Algoritma, Logika dan Komputasi, 2024)
The rapid growth of technology and the gaming industry in Indonesia, along with the increasing number of gamers, presents a significant opportunity to promote local culture. As Indonesia ranks third in the world for the number of gamers, a major challenge is the inadequate representation of local culture, often skewed towards international markets. Local game developers face barriers such as a lack of formal education and difficulties in creating culturally accurate content, despite efforts by the government and studios to enhance cultural representation. This study employs a qualitative-descriptive approach, utilizing data collection methods including interviews, observations, document studies, literature reviews, and questionnaires. The design methodology used is the Multimedia Development Life Cycle, focusing on creating a UI/UX that reflects Javanese culture and employing low poly 3D modeling to ensure accessibility and an engaging visual experience. The game titled "Mahesa: The Darkness of Ruins" is designed to increase awareness among the younger generation of Indonesian culture through local cultural elements and appealing design. Through this game, the author aims to introduce Indonesian culture to the international stage, advance the local gaming industry, and contribute to cultural preservation.